The Influence of Authentic Leadership and Perceived Organizational Support on Employee Creativity Mediated by Work Engagement PT. PLN (Persero) Bengkulu City - Haji Dede Saputra; Nasution (Jurnal Manajemen (Edisi Elektronik), 2025)
Employers required intelligent and innovative employees to devise novel method to enchange their business, including authentic leadership, the excent to which employees feel supported by their superiors, and their level of engagement at PT. PLN (Persero) in Bengkulu City. This quantitative study used first-hand information from people who filled out a questionnaire.  265 workers out of 298 workers at PT PLN (Persero) Bengkulu City were selected for this study using stratified random sampling method.  SEM (Structural Equation Modeling) with SmartPLS 3 software was used to look at the data in this study.  The study's findings led to the following conclusions: (1) authentic leadership has a positive and significant effect on employee creativity; (2) perceived organizational support does not have an effect on employee creativity; (3) authentic leadership has a significant and positive effect on work engagement; (4) perceived organizational support has a significant positive effect on work engagement; (5) work engagement has a significant positive effect on employee creativity; (6) work engagement can mediate the effect of authentic leadership on employee creativity.  (7) The impact of perceived organizational support on employee creativity is mediated by work engagement. PT PLN (Persero) Bengkulu City anticipates that this research will contribute to the resolution of challenges, particularly in the domains of authentic leadership, perceived organizational support, and the impact of work engagement on employee creativity.